Answer:
y = -6x + 4
Step-by-step explanation:
2 parallel lines should have equal slope
Rewrite 6x + y = 92
It is now y = -6x + 92. Slope is -6
So the new equation should also have -6 as the slope.
y = -6x + b
Substitute (1,-2) into this equation
-2 = -6(1) + b
-2 = -6 + b
4 = b
So equation is y = -6x + 4
Answer:
Step-by-step explanation:
I believe the answer is B) 50
Answer:
f(x) = 3x^2 - 12x - 36.
Step-by-step explanation:
f(x) =3 /2(x - 2)^2 - 24
f(x) = 3/2 (x^2 - 4x + 4) - 24
f(x) = 3/2 x^2 - 6x + 6 - 24
f(x) = 3/2 x^2 - 6x - 18
Multiply through by 2:
f(x) = 3x^2 - 12x - 36.